Surprisingly rich repertoire of Wnt genes in the demosponge Halisarca dujardini. Issue 1 (December 2016) - Borisenko, Ilya; Adamski, Marcin; Ereskovsky, Alexander; Adamska, Maja
Abstract Background Wnt proteins are secreted signalling molecules found in all animal phyla. In bilaterian animals, including humans, Wnt proteins play key roles in development, maintenance of homeostasis and regeneration. While Wnt gene repertoires and roles are strongly conserved between cnidarians and bilaterians, Wnt genes from basal metazoans (sponges, ctenophores, placozoans) are difficult or impossible to assign to the bilaterian + cnidarian orthologous groups. Moreover, dramatic differences in Wnt numbers among basal metazoan exist, with only three present in the genome ofAmphimedon queenslandica, a demosponge, and 21 in the genome ofSycon ciliatum, a calcisponge. To gain insight into the ancestral Wnt repertoire and function, we have chosen to investigate Wnt genes inHalisarca dujardini, a demosponge with relatively well described development and regeneration, and a very distant phylogenetic relationship toAmphimedon . Results Here we describe generation of a eukaryotic contamination-free transcriptome ofHalisarca dujardini, and analysis of Wnt genes repertoire and expression in this species. We have identified ten Wnt genes, with only one orthologous toAmphimedon Wnt, and six appearing to be a result of a lineage specific expansion. Expression analysis carried out byin situ hybridization of adults and larvae revealed that twoHalisarca Wnts are expressed in nested domains in the posterior half of the larvae, and six along the adult body axis, with two specific to the osculum. Strikingly, expression of one of the Wnt genes was elevated in the region undergoing regeneration. Conclusions Our results demonstrated that the three Poriferan lineages (Demospongiae, Calcarea and Homoloscleromorpha) are characterized by highly diverse Wnt gene repertoires which do not display higher similarity to each other than they do to the non-sponge (i.e. ctenophore, cnidarian and bilaterian) repertoires. This is in striking contrast to the uniform Wnt repertoires in Cnidarians and Bilaterians, suggesting that the Wnt family composition became "fixed" only in the last common ancestor of Cnidarians and Bilaterians. In contrast, expression of Wnt genes in the apical region of sponge adults and the posterior region of sponge larvae suggests conservation of the Wnt role in axial patterning across the animal kingdom.